A case of transnasal intracranial penetrating injury with skull base fracture caused by a broken golf club shaft. (May 2018) - Kato, Hideaki; Kanno, Sanae; Ohtaki, Jun; Nakamura, Yoshimi; Horita, Tetsuya; Fukuta, Mamiko; Eguchi, Kazuhito; Hassan Gaballa, Mohamed; Aoki, Yasuhiro
Graphical abstract: Highlights: Transnasal penetrating intracranial injury caused by a fractured golf club shaft. The victim was died from massive hemorrhage in a short time. Sphenopalatine artery and cavernous sinus were presumably the bleeding points. Pneumocephalus on CT and incision of the nostril were of advantage to diagnose.